Congenital glaucoma detected by unilateral megalophthalmos on prenatal sonography. Issue 8 (2nd December 2016) - Gennette, Sarah; Carlan, Steve J.; Busowski, John; Madruga, Mario; McWhorter, Jeannie
ABSTRACT: A 36‐week male fetus was noted to have isolated right megalophthalmos on prenatal ultrasound and was found to have buphthalmos and congenital glaucoma at birth. Detection of congenital glaucoma at birth may be occasionally possible if abnormal orbit dimensions are noted on late prenatal sonographic examination. Early neonatal intervention may improve the chances to retain vision. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45 :499–501, 2017